Autoestima y desarrollo de trastornos de la conducta alimentaria en adolescentes y adultos jóvenes - Ames Tejada, Allison Elizabeth (2022)
ED are mental illnesses of great relevance in the field of physical and mental health, as they have a great impact on people's quality of life and are increasingly common. Their incidence has increased from 3.4% to 7.8% of the population in the last 20 years (Galmiche et al., 2019). In Peru, between 7% and 11% of adolescents may present an ED (Chumpitaz, 2020). Studies suggest a significant relationship between self-esteem and ED. The present study seeks to describe the impact of self-esteem on the development of ED in adolescents and young adults. This information has been collected through an applied review process using the PRISMA search strategy. The data sources reviewed are: Proquest and Scopus. The results of the research indicate that self-esteem can be a risk or protective factor for the development of ED, being determinant the degree of self worth that the individual has about himself/herself, as well as the influence of other variables such as anxiety, depression or perfectionism. Thus, low self-esteem is reflected in attitudes of concern about body image and eating behaviors, which in turn is related to unhealthy weight control/diet practices and, ultimately, can trigger the pathology.